Project Clinik: A Cross-Platform Scheduling and Appointment Reservation System - Mark Angelo M. Dela Fuente; Joshua A. Facunla; Hannah Noreen F. De Guzman; Emille F. Jacinto; Justine B. Hilario; Cris Norman P. Olipas; Angelito I. Cunanan (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aimed to design, develop, and assess a cross-platform scheduling and appointment reservation system for clinics. The software development life cycle (SDLC) was used to guide the development of the system, which included planning, defining requirements, design and prototyping, development, testing, and operations and maintenance. A developmental experts research design was employed, and the technical features of the system were assessed by IT following the ISO 25010 standards, while end-users evaluated the quality of using the system based on selected ISO 25010 standards. The results showed that the SDLC was appropriate in developing the system, and both IT experts and end-users found the system to be of high quality. Based on the results, the researchers drew conclusions and provided recommendations for future studies. The study revealed that a cross-platform scheduling and appointment reservation system for clinics can be developed using the SDLC with the involvement of IT experts and end-users in the assessment process. It is crucial to incorporate the ISO 25010 standards to ensure that the system is of high quality and meets the needs of the end-users